QRS distortion increased risk re-occurrence acute coronary events (Medical Journal of Indonesia, 2007)
Nearly 50% of patients suffering inferior myocardial infarction will have complications or distinguishing features associated with an increased mortality. This study aimed to identify dominant risk factors related to re-occurrence of acute coronary events in patients with inferior myocardial infarction. This historical cohort included patients with inferior myocardial infarction who received fibrinolytic therapy at emergency department of National Cardiovascular Center Harapan Kita, Jakarta during 2001 to 2004 and was followed-up for two years. Patients with previous myocardial infarction, left bundle branch block, ventricular rhythm, and ventricular pacing were excluded. QRS distortion is ratio between J-point and R wave more than 50% at 2 or more inferior leads. Re-occurrence of acute coronary events is incident of myocardial infarction and unstable angina pectoris. Of 181 subjects with inferior AMI, there were 21 (11.6%) incidents of acute coronary event. Those who had positive than negative QRS distortion had almost three-fold increased risk for re-occurrence of acute coronary events [adjusted relative risk (RRa) 2.88; 95% confidence interval (CI) = 1.05 – 7.90]. In term of TIMI risk score, those with higher than lower risk score had 6.7 times higher risk to be re-occurrence of acute coronary events (RRa = 6.66; 95% CI = 1.94 – 22.92). However, those who had than did not have successful fibrinolysis had 57% lower risk to be re-occurrence of acute coronary event (RRa = 0.43; 95% CI = 0.18 – 1.05; P = 0.065). Re-occurrence acute coronary events were related to QRS distortion, TIMI risk score, and successful fibrinolysis. (Med J Indones 2007; 16:240-4)